2021
DOI: 10.1038/s41380-020-00990-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral contraceptive pills on mood and magnetic resonance imaging measures of prefrontal cortical thickness

Abstract: Gonadal hormones influence neuronal organization and plasticity. Yet the consequences of altering their concentrations by administering contraceptive agents, which are used by most reproductive-age women in the United States, are unclear. Cross-sectional studies have found both larger and smaller cortical regions alongside a variety of mood alterations in women who use oral contraceptive pills (OCPs) compared to naturally-cycling women. The goal of this study, therefore, was to determine whether there is an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Evidence increasingly points to considerable effects on brain circuitry and structure following administration of metabolic hormones in form of OC-use [e.g., (26,27,57)], however, we do not fully understand the action of OCs on brain and behavior. The present null finding extends the scarce literature on OCeffects on value-based decision-making, especially on the behavioral level.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence increasingly points to considerable effects on brain circuitry and structure following administration of metabolic hormones in form of OC-use [e.g., (26,27,57)], however, we do not fully understand the action of OCs on brain and behavior. The present null finding extends the scarce literature on OCeffects on value-based decision-making, especially on the behavioral level.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the different study designs may capture different populations of women. Placebo-controlled trials usually report a mood worsening within the first 6 months of COC treatment . Population-based studies, on the other hand, usually report improved mental health in long-term users of COCs (>6 months of COC use) .…”
Section: Introductionmentioning
confidence: 99%
“…To predict causality between COC use and mood, placebo-controlled, randomized clinical trials (RCTs) using different COC formulations were conducted. Most of these trials observed significantly lower mental well-being during the first few months of COC intake [11][12][13][14][15] (except for a study by Scheuringer et al 16 ), although only a few studies reported an increase in clinical depression scores. 15,17,18 Two factors may contribute to those seemingly contradictory results between non-RCTs and RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our knowledge about the effects of OCs on the female brain and behavior is still limited. The majority of studies have compared OC users to non-users ( 20 ) and a very small number of prospective studies have reported short-term effects of contraceptive use on the brain ( 21 24 ). Likewise, potential long-term effects are not well understood and it is still unknown if possible neurocognitive effects are reversible.…”
Section: Introductionmentioning
confidence: 99%